(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Obesity!! When anyone say this word what thought comes to our mind? A fat person with heavy distended abdomen, heavy obese legs, arms, puffy face. But do we think that the person who is obese suffered a lot due his/her weight. This is an era where more than 50% of the human being suffered from this major ailment which actually causes various other diseases like diabetes, hypothyroidism, hypertention, cardiopulmonary diseases. Obesity not only affect the body of a person but it has also a major impact over mind, mostly patient suffered from obesity also suffered with depression because of cutoff and rejection from the society. In Ayurveda also person who is obese/ Sthula is considered under Ninditya purusha which generally means abnormal. Modern medicine has treatment for this but to a very limited extent and it is very costly also. In Ayurveda there is vast reference for Sthaulya and its treatment. Case studies were done on Sthaulya roga in which Guggulu kalpa chikitsa was done and results were evaluated. There was drastic reduction in weight of the patients along with the reduction in inches of abdominal, arm and thigh girth within a month.